Alterations of insulin-like growth factor I (IGF-I) and estradiol serum levels in chronic hepatitis C - Adamek, Agnieszka (Termedia Publishing House, 2012)
AIM OF THE STUDY: Deregulation of insulin-like growth factor I (IGF-I) production and decreased hepatic estrogen levels were associated with development of hepatocellular carcinoma (HCC) in hepatitis C virus (HCV) infected cirrhotic patients. The aim of our study was to determine serum levels of IGF-I, insulin and 17-β estradiol (17-βE) in relation to other markers of liver injury in chronic hepatitis C (CHC) patients. MATERIAL AND METHODS: Thirty anti-viral treatment-naïve CHC patients and 10 healthy subjects were examined. HCV infection was confirmed by presence of anti-HCV and HCV-RNA in serum. Serum levels of IGF-I, insulin and of 17-βE were evaluated using ELISA methods. RESULTS: Serum levels of IGF-I and 17-βE were significantly lower in CHC patients than in controls while insulin levels were similar in both groups. A lower IGF-I level (but not the level of 17-βE) was observed in cirrhotic CHC patients in comparison to non-cirrhotic ones. Decreased serum level of IGF-I was associated with more advanced staging and liver steatosis, higher levels of alpha-fetoprotein (AFP) and gamma globulin levels, and higher aspartate transaminase (AST) activity in CHC patients. Insulin and 17-βE levels positively correlated with patient's age. A positive correlation was observed between insulin level on one hand and staging, liver steatosis and levels of gamma globulins in CHC patients on the other. A negative correlation between IGF-I and insulin levels was noted only in HCV infected patients. CONCLUSIONS: Decreased IGF-I levels and increased levels of insulin better than estradiol serum levels characterize staging and liver steatosis in CHC patients. The lower serum level of 17-βE in the CHC group than in control patients suggests that CHC patients carry higher risk of liver injury and of HCC development.